A Cadaveric Study of the Anatomical Characteristics of the Superficial Circumflex Iliac Artery Perforator - Tanvi Rao; Vijay Jaganathan; Jonathan Victor; Pappu Paramartha Lingam (Indian Journal of Plastic Surgery)
Background The superficial circumflex iliac artery perforator flap (SCIP flap) is an evolution of the conventional free groin flap. Even though the anatomical basis for SCIP flap is well established in general, the same is not described in a South Indian population.